Teater Tradisional Mendu dan Bangsawan di Asia Tenggara: Hubung Kait Sejarah dan Elemen Persembahan: Mendu and Bangsawan Traditional Theatre in Southeast Asia: The Correlation of History and Performance Elements - Rosdeen Suboh (Wacana Seni Journal of Arts Discourse, 2023)
This article was conducted due to the arising issues stating the connections between mendu or wayang mendu, and bangsawan but there is no further explanation regarding this matter. Moreover, there are statements from several scholar mention that the mendu or wayang mendu was the origin of bangsawan, but there is no detailed explanation. The data examined in this article involves: bangsawan performances that are still active in Kuala Lumpur, Kedah, and Sarawak which staged different stories; forms of bangsawan with different names in the coastal areas of West Sumatera and West Kalimantan, namely wayang (bangsawan) kampung, wayang Parsi, komedi Melayu, dul muluk and mamanda; while the mendu theatre which only staged Dewa Mendu story performed by respective active groups in Pulau Sedanau, Natuna (Riau Islands), Mempawah (Pontianak, West Kalimantan), and Malaysia (Universiti Malaya, Kuala Lumpur). All data collection was also obtained from interviews with mendu and bangsawan practitioners who are still active in both countries. From the data collected, this article only focusses on the connection between the historiography of mendu–bangsawan with the influence of Persian commercial theatre from Gujarat, especially in the period from 1870 to 1940. This is because, during that period, the bangsawan name was initially called wayang Parsi (mendu), tiruan wayang Parsi, and later became the main reference in the history of the development of traditional theatre in Southeast Asia. The results of the discussion in this article are divided into several important aspects which are: the relevance of historical aspects particularly the origin and development; conceptual elements (rituals and entertainment); language (dialogue); stage setting (acting space and curtain set); acting style (actors); and performance structure (scenes) of both theatres. Artikel ini membincangkan tentang isu perkaitan sejarah dan elemen persembahan antara teater tradisional mendu dan teater bangsawan Malaysia–Indonesia. Hal ini kerana terdapat penyataan dari beberapa kajian sarjana menyatakan bahawa teater mendu atau wayang mendu adalah asal mula bangsawan, namun tiada keterangan secara terperinci. Bagi tujuan tersebut, data yang diteliti dalam artikel adalah melibatkan: persembahan bangsawan yang masih aktif di Kuala Lumpur, Kedah, dan Sarawak yang telah mementaskan cerita yang berlainan; dan juga bentuk bangsawan dengan nama lain yang masih aktif di kawasan pesisiran Sumatera Barat serta pesisiran Kalimantan Barat iaitu wayang (bangsawan) kampung, wayang Parsi, komedi Melayu, dul muluk, dan mamanda; manakala teater mendu pula hanya mengambil data dari kumpulan yang masih aktif mementaskan satu-satunya cerita Dewa Mendu di Pulau Sedanau, Natuna (Kepulauan Riau), Mempawah (Pontianak, Kalimantan Barat), dan Malaysia (Universiti Malaya, Kuala Lumpur). Pengumpulan data juga diperoleh melalui temu ramah tokoh-tokoh mendu dan bangsawan yang masih aktif di kedua-dua negara. Dari data yang dikumpul, fokus penelitian hanya dibuat ke atas perkaitan pensejarahan mendu bangsawan dengan pengaruh teater komersial Parsi seperti dari Gujerat terutama pada tahun 1870 hingga 1940. Hal ini kerana, pada tempoh tersebut nama bangsawan awalnya telah digelar wayang Parsi (mendu), tiruan wayang Parsi, dan kemudian telah menjadi sebuah bentuk teater rakyat kaum Melayu yang menjadi rujukan utama dalam sejarah perkembangan teater tradisional di Asia Tenggara. Hasil dari perbincangan dalam artikel ini terbahagi kepada beberapa aspek penting iaitu: hubung kait mendu–bangsawan dari aspek pensejarahan seperti fakta asal-usul dan perkembangan; perkaitan elemen konsep (ritual dan hiburan); bahasa (dialog); panggung (ruang lakon dan set tirai); gaya lakon (pelakon); dan struktur persembahan (babak).